Permaafan Dan Diat Alternatif Pidana Penjara Pada Tindak Pidana Pembunuhan Biasa (Doodslag) - Hambali Yusuf; Topo Santoso; Nashriana Nashriana (Jurnal Hukum IUS QUIA IUSTUM, 2021)
The purpose of this study is to first, find the argument that forgiveness and punishment are needed as an alternative to other sanctions from imprisonment for the crime of murder. Second, to explain the criminal system in the application of forgiveness and punishment to ordinary murders in Islamic criminal law. Third, outlining/analyzing the policy of criminalizing the sanctions of Forgiveness and Diat on the crime of murder in the renewal of criminal sanctions. This type of research is a normative research. The approach is a statutory approach and a comparative approach as well as a philosophical approach. The results of the study conclude that first, an alternative to imprisonment is needed for ordinary murder. The application of forgiveness and punishment as an alternative to imprisonment for the crime of murder has a strong basis, both theoretically, philosophically, juridically, sociologically, and even the constitutional basis of the 1945 Constitution of the Republic of Indonesia. Second, in the application of forgiveness and punishment, the judge will apply it if there is forgiveness from the family victim. Third, as a renewal of sanctions, forgiveness and punishment are not a guide for judges, but as reasons for not imposing imprisonment, and choosing to impose an alternative fine to imprisonment, it is necessary to include it in the Draft Law on the Criminal Code which will be discussed. by the legislature.